A framework for the evaluation of an international graduate economic development program for nongovernmental organization leaders - Ridington, Morgan Thomas Jr. (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Curriculum Studies))--University of Stellenbosch, 2010.